Creating stiffness gradient polyvinyl alcohol hydrogel using a simple gradual freezing–thawing method to investigate stem cell differentiation behaviors. (February 2015) - Kim, Tae Ho; An, Dan Bi; Oh, Se Heang; Kang, Min Kwan; Song, Hyun Hoon; Lee, Jin Ho
Abstract: Polyvinyl alcohol (PVA) cylindrical hydrogel with a stiffness gradient was prepared using a simple liquid nitrogen (LN2 )-contacting gradual freezing and thawing method in order to investigate the effects of substrate stiffness on stem cell differentiation into specific cell types. The prepared cylindrical PVA hydrogel showed a gradually increasing stiffness along the longitudinal direction from the top at approximately 1 kPa to the bottom (LN2 contacted side) at approximately 24 kPa. From the in vitro culture of bone marrow stem cells, it was observed that each soft (∼1 kPa) and stiff (∼24 kPa) hydrogel section promotes effective neurogenesis and osteogenesis of the cells, respectively, with the tendency to gradually decrease toward the opposing characteristic's side. The stiffness gradient cylindrical PVA hydrogel fabricated using this simple gradual freezing and thawing method can be a useful tool for basic studies, including the determination of optimum stiffness ranges for a variety of stem cell differentiations, as well as the investigation of cell migration in terms of substrate stiffness.